Advertisement–programme congruence in memory of sexual fragrance advertisements. Issue 5 (5th February 2019) - Wong, Hiu Yan Amy; McClelland, Alastair; Furnham, Adrian
Summary: The current study explored the effect of sexual content in advertisements and the programme–advertisement congruence on the memory of sexual and nonsexual advertisements. Seventy participants (41 females and 29 males) were randomly allocated to one of four conditions. They viewed either The Bachelorette (sexual programme) or I'm a Celebrity… Get Me Out of Here! (nonsexual programme) with sexual or nonsexual fragrance advertisements placed within the programme. The order of the advertisements was counterbalanced across participants to control for order effects. Free and cued recall of the advertisements were assessed. As predicted, there was a main effect of advertisement type, with the sexual advertisements better recalled than the nonsexual advertisements. Contrary to our prediction, the sexual content of the programme did not have an effect on advertisement recall. There was an interaction between the advertisement type and programme type; sexual advertisements were remembered better when embedded within a sexual programme. Limitations of this study are considered.